Plant Oil Valorization by Cross-Metathesis Reactions: Synthesis of Fine Chemicals From Methyl Oleate - Trasarti, Andres Fernando (2020)
This work studies the production of high-value compounds by the cross-metathesis of methyl oleate (MO) with ethylene, cinnamonitrile and cinnamaldehyde using the 2nd generation Hoveyda-Grubbs complex (HG) as catalyst, either dissolved in toluene or supported on silica. Reactions were carried out in batch reactors between 313 and 343 K. The yield to cross-metathesis products (YC-M) for the MO cross-metathesis with cinnamonitrile and cinnamaldehyde increased with the initial molar re-actant ratio (RCN/MO, RCA/MO), reaching YC-M values of 82% and 95%, respectively, at R = 7. No catalyst deactivation took place during the 400-min catalytic runs. The liquid-phase cross-metathesis of MO with ethylene (ethenolysis) was performed over HG(10%)/SiO2 catalysts, producing 1-decene and methyl 9-decenoate, a valuable intermediate for the synthesis of pheromones. At RC2/MO = 2.5, the selec-tivity to ethenolysis products was 77% at 82% MO conversion. The MO self-metathesis was the only side reaction observed in all the catalytic tests.